Exploring the Landscape: A Bibliometric Analysis of Youth Engagement in Fitness Research and It’s Marketing Ramifications - Ayuningtyas Yuli Hapsari; Ratih Hurriyati; Heny Hendrayati; Ferry Arfiansyah; Ahmad Johan (International Journal of Economics Development Research (IJEDR), 2024)
This bibliometric study examines the academic literature related to the factors that drive the young generations to engage in physical exercise in gyms. This study focus on young generations’ motives to cope with stress relief, health awareness, lifestyle considerations, and their intersections with marketing strategies for gym industries. By quantitatively analyzing keywords trends used, this study aims to present a comprehensive analysis of the current state of research and identify knowledge gaps that could inform future research and marketing strategies. The Scopus database is utilized for data mining of the articles, and it discovered 1.593 documents to be analyzed using VOSviewer software. Based on the analysis of the research keywords, we identify five distinct clusters that will can assist future scholars to analyze the idea of the study. The results have substantial significance for scholars and professionals in the gym business, particularly those who are concerned with the health of young generations.